Leukemic changes of the brain: the involvement of the choroid plexus - Aristides Cheto de Queiroz; Dorcas Almeida Ribeiro (Arquivos de Neuro-Psiquiatria)
In the study of 38 cases of leukemia, neoplastic infiltration of the brain was the most frequent lesion, occuring in 70,5%, compared to 48,5% for hemorrhage. The leptomeninges were the most frequent site of leukemic infiltration followed by the choroid plexus (57,8%) and the nervous tissue (50%). In few cases leukemic infiltration of choroid plexus was seen in the absence of meningeal involvement. Very often the leukemic infiltration of the CNS courses without clinical manifestations. The paper points out the importance of the cytologic study of the cerebro-spinal fluid as a routine procedure in cases of leukemia, since it is well known that the therapeutic agents have difficulty in penetrating the blood-brain barrier and that foci of CNS leukemic infiltration may represent points of reactivation of the disease even during the therapeutic remission.